The factors that contributing organization commitment / Aimi Izyan Ahmad Shah - Ahmad Shah, Aimi Izyan (Faculty of Business and Management, 2010)
The title of this research is the factors that contributing organization commitment. Dependent variable of this research is organization commitment. In this research, there has Independent variable that link with the dependant variable. It is Job Satisfaction, HRM Practices and Organizational Trust. For data collection method, interview and questionnaire were used by the researcher. The questionnaire was distributed to the respondent in the organization. In conducting the study, the researcher will be used a Statistical Package for Social Science (SPSS) version 16.0. The first research question, the researcher will use mean, frequency and percentage to compute the data of the variable to determine the level of organization commitment. For the next research question, correlation will be used by the researcher to determine the relationship between the variable. Also the researcher provides the recommendation in the last chapter to improve the level of organization commitment.